Phacoemulsification and calculation of intraocular lenses in patients given keratorefractive surgery. Part 2 - I. E. Ioshin (Российский офтальмологический журнал)
Effective rehabilitation of patients with cataracts who underwent keratorefractive surgeries requires that the optical power of the IOL be calculated correctly to avoid hyperopic error. The purpose of the 2nd part of the research (for the 1st part, see ROJ, 2021; 14 (2): 55–58) is to present the results of cataract phacoemulsification in patients subjected to keratorefractive surgery based on the author’s algorithm for calculating the optical power of the IOL. Material and methods. The algorithm used optical biometry with an IOL-Master device. The main technique of improving the accuracy of IOL calculation after keratorefractive operations has been to introduce amendments to standard IOL calculation formulas. This work proposes an alternative, which consists in using the Hoffer Q formula, as it is more consistent with changes in the anterior segment of the myopic eye after keratorefractive surgery than other basic. The main distinguishing feature of the Hoffer Q formula is that the corneal refraction is not converted into the radius of curvature but is applied directly as the optical power of a “thin lens”. Results. The empirical customized correction was +1.0 D with regard to the estimated planned postoperative refraction (for patients with initial myopia from -3 to -9 D). The use of the “thin lens” principle made it possible to extrapolate this formula and apply it after LASIK surgery and after radial keratotomy. Conclusion. The proposed technique of IOL calculation was implemented for cataract phacoemulsification in over 200 patients who underwent keratorefractive surgeries. No cases of hyperopic shift of postoperative refraction were noted. The deviation from the planned myopic refraction did not exceed 1.0 D.